Metaphorical Framing of the Disenfranchised Grief: A Study of Post-APS Narratives Using Conceptual Metaphor Theory - Huma, Hafsa; Dr. Syed Zahid Ali Shah (Dialogue Social Science Review (DSSR), 2025)
This paper evaluates post-attack linguistic discourses relating to the 2014 Peshawar's Army Public School (APS) event in Pakistan using Conceptual Metaphor Theory as its analytical framework. The paper evaluates language techniques which included metaphorical expressions and euphemistic storytelling to dampen public distress and convert individual mourning into national patriotic self-sacrifice, while controlling prevailing collective memories. The study utilizes official statements alongside media reports and commemorative events alongside public responses to describe how victims received martyrdom status through rhetorical ascension to patriotic resilience. Furthermore, it interrogates how military operations were metaphorically cast as cleansing campaigns, shifting the narrative from grief and accountability to unity and vengeance. Through psycholinguistic techniques that minimize grief along with official denial victim families suffered two parallel consequences: difficulty expressing grief and long-term denial of national trauma. Through qualitative textual analysis that analyzes media texts with political statements and public memorialization the research shows how language works as an ideological management instrument after national tragedies.